2018
DOI: 10.7554/elife.39427
|View full text |Cite
|
Sign up to set email alerts
|

Ryanodine receptor dispersion disrupts Ca2+ release in failing cardiac myocytes

Abstract: Reduced cardiac contractility during heart failure (HF) is linked to impaired Ca2+ release from Ryanodine Receptors (RyRs). We investigated whether this deficit can be traced to nanoscale RyR reorganization. Using super-resolution imaging, we observed dispersion of RyR clusters in cardiomyocytes from post-infarction HF rats, resulting in more numerous, smaller clusters. Functional groupings of RyR clusters which produce Ca2+ sparks (Ca2+ release units, CRUs) also became less solid. An increased fraction of sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
166
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(199 citation statements)
references
References 56 publications
18
166
3
Order By: Relevance
“…This may be because of redundancy in the Ca 2+ ‐induced Ca 2+ release process (Cannell, Berlin, & Lederer, ) in mice, and/or because the LTCCs, and thus I Ca , which are regulated by Cav‐3 are predominantly extra‐dyadic (Glukhov et al., ; Sanchez‐Alonso et al., ), which could also explain why similar decreases in I Ca amplitude produced by Ca 2+ channel blockers, which will affect all Ca 2+ channels, inhibit release (Bryant et al., ). The TAC‐induced disruption of Ca 2+ release may, therefore, be due predominantly to disruption of the dyad (Louch et al., ), consistent with the observed decrease in JPH‐2 and with recent work showing dispersion of RyR clusters in rat myocytes in HF (Kolstad et al., ), so that RyR dispersion and loss of t‐tubular I Ca may have summative effects that impair Ca 2+ release along t‐tubules. Interestingly, however, Cav‐3 OE decreased the heterogeneity of Ca 2+ release in both sham and TAC myocytes, suggesting that Cav‐3 may increase the uniformity of t‐tubular Ca 2+ release by altering the distribution of I Ca or the response to I Ca along the t‐tubule.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This may be because of redundancy in the Ca 2+ ‐induced Ca 2+ release process (Cannell, Berlin, & Lederer, ) in mice, and/or because the LTCCs, and thus I Ca , which are regulated by Cav‐3 are predominantly extra‐dyadic (Glukhov et al., ; Sanchez‐Alonso et al., ), which could also explain why similar decreases in I Ca amplitude produced by Ca 2+ channel blockers, which will affect all Ca 2+ channels, inhibit release (Bryant et al., ). The TAC‐induced disruption of Ca 2+ release may, therefore, be due predominantly to disruption of the dyad (Louch et al., ), consistent with the observed decrease in JPH‐2 and with recent work showing dispersion of RyR clusters in rat myocytes in HF (Kolstad et al., ), so that RyR dispersion and loss of t‐tubular I Ca may have summative effects that impair Ca 2+ release along t‐tubules. Interestingly, however, Cav‐3 OE decreased the heterogeneity of Ca 2+ release in both sham and TAC myocytes, suggesting that Cav‐3 may increase the uniformity of t‐tubular Ca 2+ release by altering the distribution of I Ca or the response to I Ca along the t‐tubule.…”
Section: Discussionsupporting
confidence: 84%
“…therefore, be due predominantly to disruption of the dyad (Louch et al, 2013), consistent with the observed decrease in JPH-2 and with recent work showing dispersion of RyR clusters in rat myocytes in HF (Kolstad et al, 2018), so that RyR dispersion and loss of t-tubular I Ca may have summative effects that impair Ca 2+ release along ttubules. Interestingly, however, Cav-3 OE decreased the heterogeneity of Ca 2+ release in both sham and TAC myocytes, suggesting that Cav-3 may increase the uniformity of t-tubular Ca 2+ release by altering the distribution of I Ca or the response to I Ca along the t-tubule.…”
supporting
confidence: 90%
“…This includes loss of LTCCs along with t‐tubules, but also loss of some RyRs along Z‐lines, resulting in a more sparse distribution (see also Kolstad et al . ). However, where they are still present, LTCCs remain localized in dyads, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…RyRs are not firmly anchored within the CRU but exhibit a highly malleable organization dependent on factors such as phosphorylation status and cytosolic Mg 2+ levels. Failing cells contain an increased fraction of small CRUs, consisting of fewer RyR clusters, which can augment the SR to be undetectable, silence a Ca 2+ leak and desynchronize the overall Ca 2+ transient . According to Sachse et al, T‐system remodelling in human HF studies led to increased RyR‐sarcolemma distances while decreasing the number of junctional RyR clusters and increasing the number of nonjunctional RyR clusters.…”
Section: Arrhythmia Caused By Ion Channel Remodellingmentioning
confidence: 99%